2018
DOI: 10.1590/1981-6723.12716
|View full text |Cite
|
Sign up to set email alerts
|

Powdered yoghurt produced by spray drying and freeze drying: a review

Abstract: Yoghurt is one of the dairy products most consumed worldwide but dehydrated yoghurt is still uncommon. Considered a nutritious food, yoghurt powder could be used as an ingredient or supplement in juices, cookies, ice cream and dairy beverages. Spray drying and freeze drying are the methods most widely used to dehydrate dairy products, and the process conditions are directly associated with the production costs and value of the final product. Due to osmotic and thermal stress during dehydration, it is often nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 55 publications
2
17
1
Order By: Relevance
“…bulgaricus and rehydrated yoghurts ( Table 5 ). The current results are in a contrast with those found by Santos et al., 2018a , Santos et al., 2018b , who found that Streptococcus thermophlius usually survive more than Lactobacillus bulgaricus and that sucrose had no effect on protection of yoghurt starter culture during freeze drying. Whey protein was used as protectants and added to the drying media before freeze drying to protect the viability of yoghurt cultures during dehydration ( Martín et al., 2015 ).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…bulgaricus and rehydrated yoghurts ( Table 5 ). The current results are in a contrast with those found by Santos et al., 2018a , Santos et al., 2018b , who found that Streptococcus thermophlius usually survive more than Lactobacillus bulgaricus and that sucrose had no effect on protection of yoghurt starter culture during freeze drying. Whey protein was used as protectants and added to the drying media before freeze drying to protect the viability of yoghurt cultures during dehydration ( Martín et al., 2015 ).…”
Section: Resultscontrasting
confidence: 99%
“…It includes drying the product through sublimation at low temperatures and under vacuum. This procedure maintains the nutritional, microbiological, and sensory characteristics, and results in a dry product that rehydrates easily ( Santos et al., 2018 ). Jaruwan Chutrtong (2015) reported that freeze-dried yoghurt must be stored in dry conditions at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The populations of both starter cultures decreased to <10% of the corresponding counts in the wet blends on drying at 46 °C for 48 h (Figure 1b). The reduction in starter culture viability during drying of the blend is consistent with the results of previous studies on spray drying yoghurt [29,30].…”
Section: Resultssupporting
confidence: 91%
“…Moreover, this different due to amount of stirring during dehydration and count of batches during drying yogurt samples, sample A stirring 4 times, B stirring 5 times, and C stirring 3times. This result comparable withSantos et al, (2018), who found the yield of freeze dried yogurt was 18%.…”
supporting
confidence: 90%